EXPLORING THE ROAD SAFETY MEASURES AND BEHAVIORAL PATTERNS AMONG MEDICAL STUDENTS IN PERAMBALUR DISTRICT, TAMIL NADU: A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Road traffic accidents (RTAs) are a major public health concern, particularly among young adults. Despite increasing awareness, unsafe driving practices remain prevalent. This study assessed the knowledge, attitude, and practices (KAP) regarding road safety and their determinants among medical students in Perambalur district, Tamil Nadu. Materials and Methods: An institution-based cross-sectional study was conducted among 507 MBBS students using stratified random sampling. Data were collected through a pre-tested, validated questionnaire assessing sociodemographic characteristics and KAP on road safety. Descriptive statistics were used to summarize the data. Associations were analyzed using Chi-square tests, and independent predictors were identified using binary logistic regression. A p-value